2016
DOI: 10.1088/1475-7516/2016/05/024
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Milky Way analogues: implications for dark matter direct searches

Abstract: We study the implications of galaxy formation on dark matter direct detection using high resolution hydrodynamic simulations of Milky Way-like galaxies simulated within the eagle and apostle projects. We identify Milky Way analogues that satisfy observational constraints on the Milky Way rotation curve and total stellar mass. We then extract the dark matter density and velocity distribution in the Solar neighbourhood for this set of Milky Way analogues, and use them to analyse the results of current direct det… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
150
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(165 citation statements)
references
References 160 publications
(316 reference statements)
12
150
1
1
Order By: Relevance
“…Refs. [66,67] found that a Maxwellian speed distribution is a good fit to the speed distribution in their hydrodynamical simulations. This may be because adiabatic contraction makes the logarithmic slope of the density profile in the Solar neighbourhood closer to that of an isothermal sphere [67].…”
Section: B Hydrodynamicalmentioning
confidence: 98%
See 2 more Smart Citations
“…Refs. [66,67] found that a Maxwellian speed distribution is a good fit to the speed distribution in their hydrodynamical simulations. This may be because adiabatic contraction makes the logarithmic slope of the density profile in the Solar neighbourhood closer to that of an isothermal sphere [67].…”
Section: B Hydrodynamicalmentioning
confidence: 98%
“…In early 2016 several studies of the local dark matter distribution in MW-like galaxies were published [66][67][68]. Borzognia et al [66] selected galaxies from the EAGLE [69] and APOSTLE [70] projects with masses in the range (10 12 − 10 13 M ⊙ ) that satisfied observational constraints on the MW rotation curve and stellar mass. Kelso et al [67] [68] studied four MW-like galaxies, with masses in the range 0.7 − 0.9 × 10 12 M ⊙ with a variety of different merger histories (i.e.…”
Section: B Hydrodynamicalmentioning
confidence: 99%
See 1 more Smart Citation
“…A mass, m a = √ 2 Φ , for this second field is originated by an explicit mass term 2 Φ Φ 2 /2 in Eq. (77). In this kind of setup it is rather natural to identify the pseudoscalar component with a pseudo-Goldstone boson associated to a U (1) global symmetry carried by the complex scalar Φ and then assumes that m a m S [298][299][300].…”
Section: Scalar + Light Pseudoscalar Portalmentioning
confidence: 99%
“…Small deviations from a MB distribution are likely, as seen in numerical simulations, e.g. [42][43][44], and predicted by Earth-scattering effects, e.g. [45][46][47], but we do not consider them in this work.…”
Section: Photon Emission Scattering Ratementioning
confidence: 99%